2016
DOI: 10.1007/s11356-016-6358-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alginate on the aggregation kinetics of copper oxide nanoparticles (CuO NPs): bridging interaction and hetero-aggregation induced by Ca2+

Abstract: The stability of CuO nanoparticles (NPs) is expected to play a key role in the environmental risk assessment of nanotoxicity in aquatic systems. In this study, the effect of alginate (model polysaccharides) on the stability of CuO NPs in various environmentally relevant ionic strength conditions was investigated by using time-resolved dynamic light scattering. Significant aggregation of CuO NPs was observed in the presence of both monovalent and divalent cations. The critical coagulation concentrations (CCC) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 39 publications
8
21
0
Order By: Relevance
“…Further increase in pH resulted in charge reversal with zeta potential values of −24.76 ± 1.3 mV at pH 11 ± 0.1. These results were consistent with previous study findings [25], suggesting that the surface potential was positive when pH < pHiep and negative at pH > pHiep. In addition, NPs with zeta potential below ±15 mV were supposed to be unstable, while NPs with zeta potential higher than ±30 mV were considered stable in the solution.…”
Section: Characteristics Of Cuo Npssupporting
confidence: 94%
See 1 more Smart Citation
“…Further increase in pH resulted in charge reversal with zeta potential values of −24.76 ± 1.3 mV at pH 11 ± 0.1. These results were consistent with previous study findings [25], suggesting that the surface potential was positive when pH < pHiep and negative at pH > pHiep. In addition, NPs with zeta potential below ±15 mV were supposed to be unstable, while NPs with zeta potential higher than ±30 mV were considered stable in the solution.…”
Section: Characteristics Of Cuo Npssupporting
confidence: 94%
“…As shown in Figure 1, CuO NPs exhibit a stable and positive charge (+27.9 ± 1.3 mV) from pH 3.0-5.0. Subsequently, the zeta potential sharply decreased to the Isoelectric point (IEP) at a pHiep of approximately ~8.2 ± 0.1, which is consistent with earlier studies [9,23,25] investigating CuO NPs. Further increase in pH resulted in charge reversal with zeta potential values of −24.76 ± 1.3 mV at pH 11 ± 0.1.…”
Section: Characteristics Of Cuo Npssupporting
confidence: 91%
“…The increased agglomeration in the NCM can likely be attributed to the presence of various cations in the NCM, which compress the electrical double layer and increase the likelihood of particle–particle interactions (Prathna et al ). Divalent cations in particular, such as those in our NCM, have been demonstrated to impact the stability of NPs in aqueous media (Baalousha et al ; Miao et al ). Large agglomerates also formed in MQW, suggesting instability of the ZnO NPs in suspension, even in pure water.…”
Section: Discussionmentioning
confidence: 99%
“…Sheng et al (2016) reported that the aggregation of hematite NPs can reduce the adsorption of metal Cu (II). The effect of EPS on the stability of manufactured nanoparticles (NPs) and natural iron (hydr)oxide colloids have also been investigated by several authors (Khan et al, 2011;Miao et al, 2016;Xu et al, 2016). For instance, exopolysaccharides extracted from the bacterium Bacillus pumilus are shown to play an important role in the stability of silver NPs in water (Khan et al, 2011), and flocculent sludge-derived EPS are found to enhance the stability of CuO NPs (Miao et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of EPS on the stability of manufactured nanoparticles (NPs) and natural iron (hydr)oxide colloids have also been investigated by several authors (Khan et al, 2011;Miao et al, 2016;Xu et al, 2016). For instance, exopolysaccharides extracted from the bacterium Bacillus pumilus are shown to play an important role in the stability of silver NPs in water (Khan et al, 2011), and flocculent sludge-derived EPS are found to enhance the stability of CuO NPs (Miao et al, 2016). It has also been reported that the addition of EPS extracted from bloom-forming cyanobacteria that are ubiquitously present in eutrophic waters can greatly decrease the hydrodynamic diameters of Al2O3 colloidal particles, and the electrolyte cations can induce the aggregation of colloidal particles (Xu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%